Assessment of the effects of decision aids about breast cancer screening: a systematic review and meta-analysis. Issue 10 (6th October 2017) - Martínez-Alonso, Montserrat; Carles-Lavila, Misericòrdia; Pérez-Lacasta, Maria José; Pons-Rodríguez, Anna; Garcia, Montse; Rué, Montserrat
Abstract : Objective: The aim of this systematic review and meta-analysis of randomised controlled trials (RCTs) and observational studies is to assess the effect of decision aids (DAs) in women aged 50 and below facing the decision to be screened for breast cancer. Setting: Screening for breast cancer. Intervention: DAs aimed to help women make a deliberative choice regarding participation in mammography screening by providing information on the options and outcomes. Eligible studies: We included published original, non-pilot, studies that assess the effect of DAs for breast cancer screening. We excluded the studies that evaluated only participation intention or actual uptake. The studies' risk of bias was assessed with the Cochrane Collaboration's tool for RCTs and the National Institutes of Health Quality Assessment Tool for non-RCTs. Primary and secondary outcomes: The main outcome measures were informed choice, decisional conflict and/or confidence, and knowledge. Secondary outcomes were values, attitudes, uncertainty and intention to be screened. Results: A total of 607 studies were identified, but only 3 RCTs and 1 before-after study were selected. The use of DAs increased the proportion of women making an informed decision by 14%, 95% CI (2% to 27%) and the proportion of women with adequate knowledge by 12%, 95% CI (7% to 16%). We observed heterogeneity among the studies in confidence in the decision. The meta-analysis of the RCTs showed a significant decrease in confidence in the decision and in intention to be screened. Conclusions: Tools to aid decision making in screening for breast cancer improve knowledge and promote informed decision; however, we found divergent results on decisional conflict and confidence in the decision. Under the current paradigm change, which favours informed choice rather than maximising uptake, more research is necessary for the improvement of DAs.